EFEKTIFITAS AKUPRESUR MENGATASI MUAL MUNTAH DAN SAKIT KEPALA IBU HAMIL TRIMESTER SATU DI PUSKESMAS MURUNG PUDAK - Akmila, Rusna; Maolinda , Winda; Melviani, Melviani (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
The discomfort most often complained of by pregnant women is nausea, vomiting and headaches. This will have an impact on the mother and fetus, namely premature birth and the fetus is threatened with low birth weight (LBW), fainting and also low blood pressure. Pregnant women will be better off if they are able to overcome the problem of nausea, vomiting and headaches by using non-pharmacological complementary therapies, one of which is acupressure. Objective: This study aims to determine the effectiveness of acupressure points PC6, GV20, GB20, EX-HN1, EX-HN3, EX-HN5 to treat nausea, vomiting and headaches in first trimester pregnant women at the Murung Pudak Health Center. The research design used was an experiment with a one group pre test-post test design using the Total Sampling technique. The number of samples is 17 respondents. Time for research in January 2023. Statistical tests using the T-test. The results of the study obtained an average decrease in the frequency of nausea and vomiting before and after treatment from 8.18 to 3.65 and a decrease in the headache scale before and after treatment from 3.94 to 0.59 so that a p-value = (0.000) was obtained < ? (0.05) Conclusion: This means that there is effectiveness of acupressure points PC6, GV20, GB20, EX- HN1, EX-HN3, EX-HN5 to treat nausea, vomiting and headaches in first trimester pregnant women at the Murung Pudak Health Center in 2023.